Технологии блокчейн в концепции «умных городов» - Искров, А. С.; Курилович, К. С.; Ващило, А. А. (БНТУ, 2022)
This article considers the possible influence of modern blockchain technologies and the concept of “smart” cities. The analysis of efficiency and demand of these technologies in various sectors of economy is conducted. The article considers main steps to implementation of decentralized networks in the life of modern society.